ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN PEMALANG - Sri Mulyani, Dina; Khoiri Furqon, Imahda (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2021)
Land and Building Tax in the Rural and Urban Sector (PBB-P2) is one of the taxes managed by the Regional Government, starting from the administration process to tax collection including the exploration of its potential. Rural and Urban Land and Building Tax is a tax on land and / or buildings that are owned, controlled, and or utilized by individuals or entities, except for areas used for plantations, forestry and mining business activities. The management of land and building taxes is left to regional governments since the enactment of Law Number 28 of 2009 concerning Regional Taxes and regional levies. The purpose of this study was to determine how the land and building tax payment system in Pemalang Regency. The results showed that the effectiveness of the land and building tax payment system in Pemalang Regency was less effective. Factors that have not yet achieved the realization of land and building tax revenue include taxpayers who have not fully reported and deposited the amount that should have been paid in accordance with their tax arrears and it is hoped that public awareness will want to pay Land and Building Tax so that local revenue (PAD) can increase. The research method used in this research is interview, documentation and observation. Where the researchers conducted interviews with several local residents, and provided a questionnaire containing the effectiveness of tax collection in the area.